Microglia: roles and genetic risk in Parkinson’s disease - Trainor, Alex R.; MacDonald, Debra S.; Penney, Jay (Frontiers in Neuroscience, 2024)
The prevalence of neurodegenerative disorders such as Parkinson’s disease are increasing as world populations age. Despite this growing public health concern, the precise molecular and cellular mechanisms that culminate in neurodegeneration remain unclear. Effective treatment options for Parkinson’s disease and other neurodegenerative disorders remain very limited, due in part to this uncertain disease etiology. One commonality across neurodegenerative diseases is sustained neuroinflammation, mediated in large part by microglia, the innate immune cells of the brain. Initially thought to simply react to neuron-derived pathology, genetic and functional studies in recent years suggest that microglia play a more active role in the neurodegenerative process than previously appreciated. Here, we review evidence for the roles of microglia in Parkinson’s disease pathogenesis and progression, with a particular focus on microglial functions that are perturbed by disease associated genes and mutations.